Police Efforts in Tackling Oil Palm Theft in the Jurisdiction of the Serdang Bedagai Police - Siregar, Lengkap Suherman; Zulyadi, Rizkan; Frensh, Wenggedes (Journal of Public Representative and Society Provision, 2025)
Oil palm theft is one of the crimes that often occur in the jurisdiction of the Serdang Bedagai Police. This crime is influenced by various factors, such as the economic condition of the community, the weak plantation security system, and the existence of an organized network of theft syndicates. This study aims to analyze the factors that cause oil palm theft, the role of the police in overcoming it, and the obstacles faced in the law enforcement process. The research method used is qualitative descriptive, with a case study approach in the jurisdiction of the Serdang Bedagai Police. Data was obtained through interviews with police officers, the community, and plantation officials, as well as documentation and observations in the field. The results of the study show that the Serdang Bedagai Police have made various efforts in dealing with oil palm theft through preventive, repressive, and pre-emptive approaches. These efforts include routine patrols, cooperation with plantations, legal socialization to the community, and law enforcement against perpetrators. However, there are still obstacles such as limited human resources, low public participation in reporting crimes, and the complexity of the theft syndicate network. To overcome this obstacle, synergy between the police, the community, and plantation companies is needed in improving the security system and creating alternative economic solutions for the surrounding community. With a more comprehensive approach, it is hoped that the number of oil palm theft in this region can be significantly reduced.